Effect and interaction of TNKS genetic polymorphisms and environmental factors on telomere damage in COEs-exposure workers - Xiaoran Duan; Tao Huang; Daping Zhang; Yujie Wei; Lifeng Li; Wu Yao; Liuxin Cui; Xiaoshan Zhou; Yongli Yang; Wei Wang; Jie Zhao (Ecotoxicology and Environmental Safety, 2023)
Coke oven emissions (COEs) contain many carcinogenic polycyclic aromatic hydrocarbons (PAHs). Telomere damage is an early biological marker reflecting long-term COEs-exposure. Whereas, whether the genetic variations of telomere-regulated gene TNKS have an effect on the COEs-induced telomere damage is unknown. So we detected the environmental exposure levels, relative telomere length (RTL), and TNKS genetic polymorphisms among 544 COEs-exposure workers and 238 healthy participants. We found that the RTL of the wild homozygous GG genotype in rs1055328 locus was statistically shorter compared with the CG+CC genotype for the healthy participants using covariance analysis(P = 0.008). In the Generalized linear model (GLM) analysis, TNKS rs1055328 GG could accelerate telomere shortening (P = 0.011); and the interaction between TNKS rs1055328 GG and COEs-exposure had an effect on RTL (P = 0.002). In conclusion, this study was the first to discover the role of TNKS rs1055328 locus in COEs-induced telomere damage, and proved that chromosomal damage was a combined consequence of environmental and genetic factors.